f



how to "(1-3*x^2)/(1-3*x+x^2+2*x^3) => 1/(1-2*x) + x/(1-x-x^2)"?

hi

 normal(1/(1-2*x) + x/ (1-x-x^2),expanded);
1/(1-2*x) + x/(1-x-x^2) => (1-3*x^2)/(1-3*x+x^2+2*x^3)
how to do the reverse?

0
dillogimp
4/9/2007 12:48:38 PM
comp.soft-sys.math.maple 4344 articles. 3 followers. Post Follow

1 Replies
2142 Views

Similar Articles

[PageSpeed] 55

dillogimp@gmail.com writes:

>  normal(1/(1-2*x) + x/ (1-x-x^2),expanded);
> 1/(1-2*x) + x/(1-x-x^2) => (1-3*x^2)/(1-3*x+x^2+2*x^3)
> how to do the reverse?

convert(%,parfrac,x);

-- 
Joe Riel
0
Joe
4/9/2007 1:46:44 PM
Reply: